A novel syndrome of hypohidrosis and intellectual disability is linked to COG6 deficiency. Issue 7 (20th April 2013) - Shaheen, Ranad; Ansari, Shinu; Alshammari, Muneera J; Alkhalidi, Hisham; Alrukban, Hadeel; Eyaid, Wafaa; Alkuraya, Fowzan S
Abstract : Background: Numerous syndromic forms of intellectual disability have been described including those with abnormal sweating pattern. Purpose: To describe the clinical and molecular analysis of a large multiplex consanguineous Saudi family with an unusual constellation of severe intellectual disability, hypohidrosis, abnormal teeth, and acquired microcephaly. Methods: Clinical evaluation, autozygosity mapping, exome sequencing, and expression analysis. Results: Autozygosity mapping revealed a single critical locus corresponding to chr13:39 338 062–40 857 430. Exome sequencing uncovered a deep intronic (NM_020751.2:c.1167–24A>G) variant in COG6 that largely replaces the consensus acceptor site, resulting in pronounced reduction of the normal transcript and consequent deficiency of COG6 protein. Patient cells also exhibited pronounced deficiency of STX6, consistent with the established stabilising effect of COG6 on STX6. Four additional patients representing two families of the same tribal origin as the original family were found to have the same mutation, confirming a founder effect. Remarkably, none of the patients displayed any detectable abnormality in the glycosylation pattern of transferrin, which contradicts a previously published report of a patient whose abnormal glycosylation pattern was presumed to be caused by a missense variant in COG6. Conclusions: Our data implicate COG6 in the pathogenesis of a novel hypohidrotic disorder in humans that is distinct from congenital disorders of glycosylation.